#TITLE_ALTERNATIVE# - RAHAYU SOEBARDI (NIM 24895005), HARIYANTI
Composite membrane is an asymetric membrane consisting of two layers i.e a support porous layer and a dense active layer from different materials. The advantage of using this composite membrane is that each layer can be optimized to obtain a better performance of membrane. Optimation of the active layer is carried out to have a high selectivity while optimation of the support layer is carried out to obtain both permeation rate and high mechanical strength of membrane. Support layer is made by phase inversion technique and coating is carried out by interfacial polimerization of p-phenilene diamine (PPD) and trimesoyl chloride (TMC). In this experiment , the process of reverse osmosis on waste of disperse dyes was conducted in order to obtain a reused permeate for textile processing water, dyestuff retake and concentrated waste. For those purposes above, a composite membrane was made with a composition of 16% polysulfone (PSf), 16% polyethyleneglycol (PEG) and 68% dimethylacetamide (DMAc) . The dense active layer was made by interfacial polymerization using 1.35% PPD and a TMC solution having a concentration of 0.05 ; 0.10 and 0.15% The results of characterization on both membrane and permeate showed that a composite membrane , with a composition of TMC 0.05% -PPD 1.35% gave the optimal performance. A rejection of 90% the disperse dyes could be obtain with an applied pressure of 20 bar - Moreover, the permeate can be reused for textile water processing.